The ZtvelB Gene Is Required for Vegetative Growth and Sporulation in the Wheat Pathogen Zymoseptoria tritici - Tiley, Anna M. M.; White, Hannah J.; Foster, Gary D.; Bailey, Andy M. (Frontiers in Microbiology, 2019)
The ascomycete fungus Zymoseptoria tritici is the causal agent of Septoria Tritici Blotch, a major disease of wheat across Europe. Current understanding of the genetic components and the environmental cues which influence development and pathogenicity of this fungus is limited. The velvet B gene, velB, has conserved roles in development, secondary metabolism and pathogenicity across fungi. The function of this gene is best characterised in the model ascomycete fungus Aspergillus nidulans, where it is involved in co-ordinating the light response with downstream processes. There is limited knowledge of the role of light in Z. tritici, and of the molecular mechanisms underpinning the light response. We show that Z. tritici is able to detect light, and that the vegetative morphology of this fungus is influenced by light conditions. We also identify and characterise the Z. tritici velB gene, ZtvelB, by gene disruption. The ztvelB deletion mutants were fixed in a filamentous growth pattern and are unable to form yeast-like vegetative cells. Their morphology was similar under light and dark conditions, showing an impairment in light-responsive growth. In addition, the ztvelB mutants produced abnormal pycnidia that were impaired in macropycnidiospore production but could still produce viable infectious micropycnidiospores. Our results show that ZtvelB is required for yeast-like growth and asexual sporulation in Z. tritici, and we provide evidence for a role of ZtvelB in integrating light perception and developmental regulation in this important plant pathogenic fungus.